2023
DOI: 10.3389/fmed.2023.1265860
|View full text |Cite
|
Sign up to set email alerts
|

Safety and efficacy of remimazolam for general anesthesia in elderly patients undergoing laparoscopic cholecystectomy: a randomized controlled trial

Keum Young So,
Jihwan Park,
Sang Hun Kim

Abstract: IntroductionThere is insufficient evidence regarding the efficacy and safety of remimazolam in elderly patients. Therefore, this study evaluated the differences in the anesthesia characteristics and perioperative hemodynamic profiles of elderly patients receiving total intravenous anesthesia with remimazolam or propofol.MethodsEighty-four patients aged >65 years with an American Society of Anesthesiologists physical status of I–III were randomly assigned to Group R (receiving remimazolam, n = 42) or Gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 33 publications
0
0
0
Order By: Relevance
“…Previous studies on remimazolam have reported that when flumazenil is administered postoperatively, the emergence time is shorter than that with traditional anesthetic drugs [41][42][43]. In the absence of flumazenil, the emergence time was not different or longer [44,45]. The results of the present study can also be attributed to the administration of flumazenil during the emergence phase.…”
Section: Discussionsupporting
confidence: 53%
“…Previous studies on remimazolam have reported that when flumazenil is administered postoperatively, the emergence time is shorter than that with traditional anesthetic drugs [41][42][43]. In the absence of flumazenil, the emergence time was not different or longer [44,45]. The results of the present study can also be attributed to the administration of flumazenil during the emergence phase.…”
Section: Discussionsupporting
confidence: 53%